A systematic study of rheological properties of waterironoxide nanofluids with graphene nanoflakes - Arifutzzaman, A.; Ismail, Ahmad Faris; Alam, Md. Zahangir; Khan, Ahsan Ali; Saidur, Rahman (Institute of Physics Publishing, 2020)
Magnetic properties are the concentrated studies in iron oxide based magnetic nanofluid area; however very limited number studies have been conducted on the psychical properties of this nanofluid. The main objective of this study is to investigate the viscosity properties of Maghemite: MH (iron oxide) nanoparticles dispersed de-ionized water (DW) nanofluids (DW-MH) for the addition of graphene (Gr) nanoflakes. DW-MH nanofluids were prepared by two steps technique and graphene was added with the aid of sonication and stirring process. Viscosity were measured for every samples varied for the loading of graphene in DW-MH nanofluids. Every measurement was conducted in rising temperature varied within 20 - 60°C. Effect of both of loading of graphene and rising temperature on the viscosity properties of the fluid were systemically analysed. Prepared nanofluids were kept stabile about 30 days without any visible sedimentations. After the addition of graphene in the DW-MH nanofluids the viscosity of the final nanofluid samples was increased with the increasing loading of graphene nanoflakes. It was also detected that, hybrid nanofluids sample's viscosity was decreasing for the increasing temperature. This nanofluid can be the viable replacement for the heat transfer purpose in the energy harvesting and storage applications due to the good physical stability.